Implementasi Kebijakan Pengembangan Potensi Sektor Pariwisata di Kabupaten Kepulauan Anambas - Suryanti Nengsih, Neng; Usman Siam, Nurbaiti; Ferizone, Ferizone; Rasid, Dede; Ramdani, Yudi; Normala, Arfia (STISIPOL Raja Haji, 2023)
Abstract Anambas Islands Regency as a new Regency still does not have a tourism sector development plan in the form of RIPPDA (Regional Tourism Development Master Plan). Meanwhile, the RIPPDA policy is really needed in the tourism development process itself. The absence of a RIPPDA-style policy for tourism development has an impact on SOP (Standard Operating Procedures) in its development, development of tourism human resources, forms of coordination that are still not realized, and community support that is still lacking in participation. The aim of this research is to find out the Implementation of Tourism Sector Potential Development Policy in Anambas Islands Regency. This type of research uses descriptive qualitative. The sampling technique used was purposive sampling, where the population consisted of 56 officials from the Department of Tourism and Culture, 9 tourism awareness groups, 10 district officials, 10 culinary tourism business actors and a sample of 5 people. Research Locations in Anambas Islands Regency and Office of Tourism and Culture. Sources and types of data in the form of primary and secondary data. Data collection techniques in this study are observation, interviews and documentation. This study uses the theory of Van Meter and Van Horn (Herabudin; 2016: 72-73) stating that there are 6 variables that influence Policy Implementation. Based on the results of the study, it was concluded that the Implementation of Tourism Sector Potential Development Policy in Anambas Islands Regency did follow the guidelines according to procedures, namely SOP, RENSTRA in its policies. It's just that there has not been the formation of its own regulations in the form of a Regional Tourism Development Master Plan (RIPPDA). There must be a policy in the form of RIPPDA and there must be funds and competent human resources in tourism development in Anambas Islands Regency. Abstrak Kabupaten Kepulauan Anambas sebagai Kabupaten baru masih belum memiliki perencanaan pembangunan sektor pariwisata dalam bentuk RIPPDA (Rencana Induk Pengembangan Pariwisata Daerah). Sementara kebijakan RIPPDA sangat di butuhkan dalam proses pengembangan pariwisata itu sendiri. Belum adanya kebijakan bentuk RIPPDA ini bagi pengembangan pariwisata, berdampak kepada SOP (Standar Operating Prosedure) dalam pengembangannya, pembangunan SDM pariwisata, bentuk koordinasi yang masih kurang terealisasi, serta dukungan masyarakat yang masih kurang ikut berpartisipasi. Tujuan penelitian mengetahui Implementasi Kebijakan Pengembangan Potensi Sektor Pariwisata Di Kabupaten Kepulauan Anambas. Jenis penelitian menggunakan deskriptif kualitatif. Teknik penggunaan sampel menggunakan purposive sampling, dimana populasi berjumlah 56 orang aparatur Dinas Pariwisata dan Kebudayaan, 9 kelompok sadar wisata, 10 pihak kecamatan, 10 pelaku usaha wisata kuliner dan sampel berjumlah 5 orang. Lokasi Penelitian di Kabupaten Kepulauan Anambas dan Kantor Dinas Pariwisata dan Kebudayaan. Sumber dan jenis data berupa data primer dan sekunder. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Penelitian ini menggunakan teori dari Van Meter dan Van Horn (Herabudin; 2016: 72-73) menyatakan ada 6 variabel yang mempengaruhi Implementasi Kebijakan. Berdasarkan hasil penelitian diambil kesimpulan Implementasi Kebijakan Pengembangan Potensi Sektor Pariwisata Di Kabupaten Kepulauan Anambas memang mengikuti acauan sesuai prosedur yaitu SOP, RENSTRA dalam kebijakannya. Hanya saja belum terbentuknya peraturan sendiri dalam bentuk Rencana Induk Pengembangan Pariwisata Daerah (RIPPDA). Harus adanya kebijakan dalam bentuk RIPPDA dan harus adanya dana serta sumber daya manusia yang berkompeten dalam pengembangan pariwisata di Kabupaten Kepulauan Anambas.